Estudio sociolinguístico de la vitalidad del kichwa en la comunidad Chaupiloma, parroquia Tupigachi, cantón Pedro Moncayo. - Pujota Cabascango, Carmen Aida (2018)
The research work is aimed at determining the vitality of the Kichwa language in the Chaupiloma community, located in the province of Pichincha. The socio historical context of the community is taken into consideration. The background of the research, the linguistic and sociolinguistic concepts related to the subject are reviewed. Then, with the methodology for the case study, the data is collected to study the situation of the Kichwa in the different levels of the community. Once all the necessary information has been collected and, according to the analysis of all the compiled data, it can be concluded that there is an average assessment of the Kichwa language in this community. The majority of members of the community are in favor of a bilingual school and that children speak Kichwa. However, there is a percentage of families that would prefer to be taught English. They think that to learn English, the Kichwa must be forgotten. Information is needed that knowing first Kichwa as their own language and Spanish would make it easier for them to learn any other language such as English.